Jejak Pemikiran Al-Gazali dalam Tradisi Pendidikan Pesantren - A Washil (Institut Ilmu Keislaman Annuqayah, 2016)
Pesantren (Islamic boarding school) tradition can not be separated from the influence of Abu> Ha>mid al-Gaza>li>. This thought became the foundation to see the traces left by this hujjatul Isla>m in pesantren’s scientific tradition; what have became tradition, and what have changed and developed in the tradition itself. This study shows that the thought of al-Gaza>li> influence several aspects (1) ontology about the nature and origin of science, it’s quality and position, which is linked to the learning process, (2) classification of science that is read sub-ordinatively, classificatively, even dichotomous, (3) the orientation and development of science in the education process that oriented to the hereafter life and worldly benefit. But in education process, every pesantren has their own interpretation. It is caused by differences in readings and adjustments to local circumstances. Therefore the thought of al-Gaza>li> is not always intact in education process. Most actually showed irregularities. It is caused by the dynamics of the social history, cultural and political of Indonesian. Readings and interpretation of al-Gaza>li> thought in pesantren tradition is also dynamic, in the sense of showing the progress from period to period.